2012
DOI: 10.1051/0004-6361/201118020
|View full text |Cite
|
Sign up to set email alerts
|

The bispectrum covariance beyond Gaussianity

Abstract: Context. To investigate and specify the statistical properties of cosmological fields with particular attention to possible non-Gaussian features, accurate formulae for the bispectrum and the bispectrum covariance are required. The bispectrum is the lowest-order statistic providing an estimate for non-Gaussianities of a distribution, and the bispectrum covariance depicts the errors of the bispectrum measurement and their correlation on different scales. Currently, there do exist fitting formulae for the bispec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…In the case of third-order cosmic shear statistics, however, Simon et al (2015) recently have found, at least in current state-of-the-art surveys, that a Gaussian likelihood is a reasonably good approximation. This agrees with results for the bispectrum covariance put forward by Martin et al (2012). As an additional remark, objections against the use of Gaussian likelihoods as a "safe default" have been raised in cases where one lacks knowledge of the exact form of the likelihood, as pointed out, for example, in power spectrum analyses by Carron (2013) and Sun et al (2013).…”
Section: Introductionsupporting
confidence: 85%
“…In the case of third-order cosmic shear statistics, however, Simon et al (2015) recently have found, at least in current state-of-the-art surveys, that a Gaussian likelihood is a reasonably good approximation. This agrees with results for the bispectrum covariance put forward by Martin et al (2012). As an additional remark, objections against the use of Gaussian likelihoods as a "safe default" have been raised in cases where one lacks knowledge of the exact form of the likelihood, as pointed out, for example, in power spectrum analyses by Carron (2013) and Sun et al (2013).…”
Section: Introductionsupporting
confidence: 85%
“…Therefore we would like to correct this effect by multiplying a factor shown in Hartlap et al [44]. For N R independent simulations, an unbiased estimator of the inverse covariance is as follows [e.g., 44,45]: (29) for N R − 2 > p, where p is the number of bins in the spectra. For our tomographic analysis with l max = 2000, the dimensions of the resulting covariance matrices are 30 × 30, 345 × 345, and 375 × 375 for the power spectrum, bispectrum, and their joint covariance, respectively.…”
Section: Signal-to-noise Ratiomentioning
confidence: 99%
“…Only the first term in Equation ( 12) is usually discussed in previous statistical analyses of the cosmological fields in the literature [7,29] except for Kayo et al [17], just because of simplicity and/or difficulty of calculation of the last four terms (see [e.g., 30,31] for real-space analyses of third-order lensing measurements). We will carefully examine how well the approximation of Gaussianity (here, the word "Gaussianity" means that the covariance matrix of the power spectrum and bispectrum is described by only the first term of Equations 8 and 12) is valid for computing the bispectrum covariance and its impact on cosmological parameter estimations, by comparing with the fully nonlinear covariance matrix measured from a large ensemble of ray-tracing simulations.…”
Section: B Covariance Matrices Of the Lensing Power Spectrum And Bisp...mentioning
confidence: 99%
“…Skewness and kurtosis are commonly used to measure the signal Gaussian characteristic in the engineering field. 24,25 The skewness is the third-order moments of signal and the kurtosis is the fourth-order moments of signal.…”
Section: Methodsmentioning
confidence: 99%